Rethinking urban sustainability using fuzzy cognitive mapping and system dynamics - Assunção, E.; Ferreira, F.; Meidute-Kavaliauskiene, I.; Zopounidis, C.; Pereira, L.; Correia, R. (International Journal of Sustainable Development and World Ecology, 2020)
The extant literature reveals a growing need to rethink urban sustainability. Sustainable urban development is becoming more important to city strategic planning since sustainability is a critical aspect of environmental protection, social cohesion, and economic growth. However, decisions are currently not always taking into account the need to maintain sustainability because either decision makers do not fully understand the decision problems at hand or they do not focus on finding realistic, contextualized solutions. In addition, most existing models of urban sustainability assessment are static. Therefore, new urban sustainability assessment systems based on landsenses ecology are needed, which should combine natural elements, physical senses, and psychological perceptions, and assist decision makers develop successful management policies. Using fuzzy cognitive mapping and system dynamics, this study sought to develop a fresh, holistic perspective on urban sustainability. Based on the knowledge and experience of a panel of experts in urban development, some of the most significant determinants of urban sustainability were identified, namely: sustainable construction; urban planning and/or design; health; economy; culture, citizenship, and education; environmental quality; public policies and governance; and mobility and/or accessibility. The results obtained were validated both by the panel members and the director of the Department of Urban Planning of the Lisbon City Council, Portugal. The advantages and limitations of our approach are also discussed, as well as recommendations for future research.